Implementasi Prinsip Etika Bisnis Islam dalam Strategi Pemasaran Produk UMKM: Studi Kasus Pandawa Bakery Nganjuk - Ahmad Maulana; Imro'atus Siti Hamidah (AGHNIYA : Jurnal Ekonomi Islam, 2026)
This study analyze the implementation of Islamic business ethics in the marketing strategy of Pandawa Bakery SMEs using a qualitative case study approach. Data were obtained through interviews, observations, and documentation. The results show the implementation of the 4P marketing mix, including product, price, place, and promotion. Pandawa Bakery maintains product quality, sets fair prices, and applies the principles of tawhid, justice, responsibility, free will, and truthfulness in marketing activities. The implementation of these Islamic business ethics principles has increased consumer trust and supported business sustainability in a highly competitive MSMEs market.